2017
DOI: 10.22631/ijaep.v6i3.184
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between flat feet and cavus foot with body mass index in girl students

Abstract: ABSTRACT:Background and Aims: The aim of this study was to investigate the relationship between flat feet and cavus foot with body mass index in girl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Result of the study is in line with the indings of a study done by Ganu SS, Panhale V 2013 (Ganu andPanhale, 2013) that showed an excessive increase in weight due to obesity leads to an increase in forces around weightbearing areas of the foot that may produce a negative Graph 6: Correlation between WHR and Rt NDT in obese subjects Graph 7: Correlation between W/H and Lt NDT in Obese subjects effect on the mechanics of the lower limbs and feet. Some studies had shown that an increase in body weight alter the overall biomechanical functioning of the foot structures as seen in the lat foot in all ages, including children and adults both (Hajirezaei et al, 2017). Universal reasons for gain in weight are lack of physical exercise and imbalance in overall consuming and expending food energies.…”
Section: Resultsmentioning
confidence: 99%
“…Result of the study is in line with the indings of a study done by Ganu SS, Panhale V 2013 (Ganu andPanhale, 2013) that showed an excessive increase in weight due to obesity leads to an increase in forces around weightbearing areas of the foot that may produce a negative Graph 6: Correlation between WHR and Rt NDT in obese subjects Graph 7: Correlation between W/H and Lt NDT in Obese subjects effect on the mechanics of the lower limbs and feet. Some studies had shown that an increase in body weight alter the overall biomechanical functioning of the foot structures as seen in the lat foot in all ages, including children and adults both (Hajirezaei et al, 2017). Universal reasons for gain in weight are lack of physical exercise and imbalance in overall consuming and expending food energies.…”
Section: Resultsmentioning
confidence: 99%